2016
DOI: 10.1590/1809-2950/14415623012016
|View full text |Cite
|
Sign up to set email alerts
|

Pacientes com doença de Parkinson sob assistência fisioterapêutica apresentam parâmetros pulmonares melhores do que controles sedentários

Abstract: | The aim of this study was to investigate the pulmonary parameters (spirometry and impulse oscillometry) of patients with Parkinson disease (PD) and healthy control peers, comparing the values of the subjects that were participating or not on a physiotherapeutic assistance program. Thirty-seven subjects were divided into four groups: two were formed by patients with PD (practitioners and non-practitioners of a physiotherapeutic protocol performed twice a week during 6 months) and the other two groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Foram empregados como critérios de inclusão, idosas cooperativas 16,19 , com boa cognição 20 , conscientes 19 , portadoras de doenças cardíacas, metabólicas, renais e hepáticas, obesas, sedentárias 19 , que responderam ao Questionário estratificado de risco cardiovascular (QERC) e que concordaram em assinar o Termo de consentimento livre e esclarecido (TCLE). Como critérios de exclusão utilizou--se a idade inferior a 65 e maior que 85 anos, com déficit cognitivo elevado 7,10,16,[20][21][22][23][24][25] , traqueostomizadas 19 , fumantes 7,10,19,24,26,[27][28][29] , portadoras de doenças respiratórias 7,8,16,21,22,28-30 e neurológicas 10,23,25,30,31 , cadeirantes 16,21,25,28,29 , acamadas 16 , com demência e que expuseram quaisquer condições que as impossibilitaram de realizar os exercícios propostos. Os dados para a cirtometria torácica foram comparados por das médias e dos desvios-padrões entre a primeira e a oitava visitas respectivamente, antes e após a intervenção, sendo realizadas as circunferências torácicas nos pontos anatômicos: axilar,…”
Section: Metodologiaunclassified
“…Foram empregados como critérios de inclusão, idosas cooperativas 16,19 , com boa cognição 20 , conscientes 19 , portadoras de doenças cardíacas, metabólicas, renais e hepáticas, obesas, sedentárias 19 , que responderam ao Questionário estratificado de risco cardiovascular (QERC) e que concordaram em assinar o Termo de consentimento livre e esclarecido (TCLE). Como critérios de exclusão utilizou--se a idade inferior a 65 e maior que 85 anos, com déficit cognitivo elevado 7,10,16,[20][21][22][23][24][25] , traqueostomizadas 19 , fumantes 7,10,19,24,26,[27][28][29] , portadoras de doenças respiratórias 7,8,16,21,22,28-30 e neurológicas 10,23,25,30,31 , cadeirantes 16,21,25,28,29 , acamadas 16 , com demência e que expuseram quaisquer condições que as impossibilitaram de realizar os exercícios propostos. Os dados para a cirtometria torácica foram comparados por das médias e dos desvios-padrões entre a primeira e a oitava visitas respectivamente, antes e após a intervenção, sendo realizadas as circunferências torácicas nos pontos anatômicos: axilar,…”
Section: Metodologiaunclassified
“…However, few studies approach interventions based on physical activity programs, whose main outcomes are the limitations related to ventilatory variables [ 10 , 11 ]. The existing ones use incentive spirometry [ 12 , 13 ], while few studies approach physical activities and/or ventilatory patterns [ 4 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been currently reported that more people in this population die from pneumonia than same-age older adults [3] and that respiratory problem share the main cause of death in PD [1,2]. Besides the mortality rates, respiratory limitations also impair PD patients' overall functioning, causing them to progressively lose their independence and quality of life [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations